Increased risk of suicidal ideation and/or self-harm in co-morbid insomnia and obstructive sleep apnea (COMISA) - Saurabh Kalra; Nandakumar Nagaraja; Deepak Kalra (Sleep Epidemiology)
Background: Obstructive sleep apnea (OSA) and insomnia are both associated with suicidal ideation (SI), but it is not known if co-morbid insomnia and obstructive sleep apnea (COMISA) has a synergistic effect. We aim to study the association of symptoms of insomnia, OSA, and COMISA with self-reported risk of SI and/or self-harm. Methods: Using cross-sectional data from the National Health and Nutrition Examination Survey (2005–2008) (n = 5,834), we examined the odds of self-reported risk of SI and/or self-harm (past 12-months) with insomnia symptoms, high-risk for OSA, and probable COMISA groups. Insomnia symptoms were identified as having trouble attaining sleep, awakening in between sleep, early awakening on more than 15 nights/month, or diagnosed by physician. High-risk for OSA was assessed by commonly used STOP-Bang questionnaire. Probable COMISA was identified if respondents had both insomnia symptoms and high-risk for OSA. Multiple logistic regression analyses examined the associations, both unadjusted and adjusted for demographics, health behaviors, and depressive symptoms. Results: Self-reported risk of SI and/or self-harm was likely to be more common among respondents with probable COMISA (AOR 3.24, 95 % CI 1.78–5.87) relative to respondents with no sleep disorder symptoms. The increase in odds for self-reported risk of SI and/or self-harm with probable COMISA compared to insomnia symptoms or high-risk for OSA alone suggests an underlying synergistic effect (Synergy Factor = 2.38). Conclusion: COMISA is associated with increased risk of SI and/or self-harm. Suicide prevention efforts should focus on multimorbidity (two or more physical/mental medical conditions) to identify high-risk groups.